Conformational Flexibility of DNA. - Marko, Andriy; Denysenkov, Vasyl; Margraf, Dominik; Cekan, Pavol; Schiemann, Olav; Sigurdsson, Snorri Th.; Prisner, Thomas F. (Journal of the American Chemical Society, 2011)
Pulsed Electron-Electron Double Resonance (PELDOR) on double-stranded DNA (ds-DNA) was used to investigate the conformational flexibility of helical DNA. Stretching, twisting, and bending flexibility of ds-DNA was determined by incorporation of two rigid nitroxide spin labels into a series of 20 base pair (bp) DNA duplexes. Orientation-selective PELDOR experiments performed at both X-band (9 GHz/0.3 T) and G-band (180 GHz/6.4 T) with spin label distances in the range of 2-4 nm allowed us to differentiate between different simple models of DNA dynaniics existing in the literature. All of our experimental results are in full agreement with a dynamic model for ds-DNA molecules, where stretching of the molecule leads to a slightly reduced radius of the helix induced by a cooperative twist-stretch coupling.